Molecular evidence for deeper diversity in Australian Tanypodinae (Chironomidae): Yarrhpelopia and related new taxa - Cranston, Peter S.; Krosch, Matt; Baker, Andrew M. (Zootaxa, 2021)
The diversity and endemism of Australian Tanypodinae (Diptera: Chironomidae) has been unclear from morphological comparisons with well-grounded northern hemisphere taxonomy. As part of a comprehensive study, here we focus on one of the few described endemic genera, Yarrhpelopia Cranston. Extensive and intensive new sampling and newly-acquired molecular data provides clarity for the type species, Yarrhpelopia norrisi Cranston and allows recognition of congeners and potential sister group(s). We describe Yarrhpelopia acorona Cranston & Krosch sp. n., and we recognise a third species from Western Australia, retaining an informal code ‘V20’ due to inadequate reared / associated material for formal description. We recognise a robust clade Coronapelopia Cranston & Krosch gen. n., treated as a genus new to science for two new species, Coronapelopia valedon Cranston & Krosch sp. n. and Coronapelopia quadridentata Cranston & Krosch sp. n., from eastern Australia, each described in their larval and pupal stages and partial imaginal stages. Interleaved between the independent new Australian clades Yarrhpelopia and Coronapelopia are New World Pentaneura and relatives, that allow a tentative inference of a dated gondwanan (austral) connection. Expanded sampling indicates that Y. norrisi, although near predictably present in mine-polluted waters, is not obligate but generally indicates acidic waters, including natural swamps and Sphagnum bogs. The inferred acidophily, including in drainages of mine adits, applies to many taxa under consideration here.